Job Loss Social Security (JKP) under Government Regulation No. 37 of 2021 as a Form of Protection for Laid-off Workers: A Normative Analysis - Husni, Lalu; Suryani H, Any; Cahyowati, RR.; Umam, Khairul (Research Horizon, 2023)
The aim of this research is to analyze Job Loss Social Security (JKP) as regulated in Government Regulation No. 37 of 2021 and assess its effectiveness in providing protection for workers. The research adopts normative legal research methods, utilizing a statutory approach and a conceptual approach. In conclusion, JKP, as outlined in Government Regulation No. 37 of 2021, is associated with the Implementation of the Job Loss Social Security Program, managed by BPJS Employment and the Central Government. Participants in the JKP program, namely workers, are entitled to benefits in the form of cash, access to market information, and job training. Despite workers experiencing benefits when submitting claims to BPJS Employment, the research indicates that JKP, based on Government Regulation No. 37 of 2021, has not fully provided adequate protection for workers. Several obstacles have been identified in its implementation, including insufficient socialization of JKP by BPJS Employment, participant registration being handled by company administrators leading to mis-targeting, limited technological literacy among workers, undocumented layoffs, and a lack of direct connectivity between the JKP application and the "Ready to Work" application at the Manpower Service, which is not directly linked to BPJS Employment.